Design build the application analysis satisfaction visitors in the library and chancery east java - Ashari, Pangestika Ayu; Hariadi, Bambang; Sulistiowati, Sulis (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
On the processing officers are still use microsoft excel for performing calculations customer satisfaction that require a long process in the questionnaire and will have an impact on delays in the construction of the evaluation.On a calculation the questionnaire is only in the average satisfaction users and descriptive analysis.In the process of making final report was late as service representative difficulties in the decision to improve the service.For want of customer services will continue to increase who made the gap between hope users and library service.So based on these problems, then required analysis users application satisfaction library. The application can help raise, store, cultivate all the questionnaire at a time and he knows the gap between hope and the fact that able to improve services properly.Then will be tested validity and reliabilitasnya employing correlation product momment pearson and cronbach alpha.After a questionnaire valid data and it is reliable, then will be calculation using modeling gap analysis. With the application it may help staff of the agency library and chancery east java to analyse satisfaction visitors exact in service of the library.